IMPIAN YANG TERABAIKAN - Amrunsyah (LEGALITE, 2019)
This paper is entitled "The Neglected Dream" (Implementation of the Purpose of Law and Criminal Law in Indonesia). Law and the purpose of law have interrelated and inseparable links. The law always plays an important role in a country even the law has a multifunction with the aim of the public good in order to achieve justice, legal certainty, order, expediency, and others. However, this is far from the fire. That is, the public is only given the wind of heaven and dreams that wash away while the state authorities use the law as a tool to suppress society, so that society can be positioned in accordance with the desires of the state authorities. The implementation of the law and the purpose of the law in force in Indonesia is clearly visible, so through a number of legal theories set forth in this paper will be a little stomping for anyone who understands it when compensating for the facts that occur in the midst of society. In fact, for people who want to get legal justice but in reality are entangled in the law. The government should be serious in responding to this because the people have given full mandate to manage this country, including in dealing with legal issues, both in terms of legal structure, legal substance and legal culture played by law enforcement.